REDUCING SOPHOMORE STUDENTS’ DILEMA IN CREATING AN APPEALING TEACHING MEDIUM THROUGH SLIDESGO USAGE - Lulud Oktaviani; Fatimah Mulya Sari (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2020)
Teachers is not only teaching or delivering materials in a class but also being a professional in all aspects of teaching. Teachers cannot ignore their students’ understanding or characteristics in every teaching and learning activity. Moreover, a teacher is considered as a professional job in Indonesia. Thus, they also get additional payment for being a professional as long as they have got a certificate of professionalism. As sophomore students of English Literature in Universitas Teknokrat Indonesia are having some pedagogical subjects which give them a choice to be an English teacher in the future, they take Teaching Material Design (TMD) in their fourth semester. The subject covers how to design a teaching set, prepare a material and media, and learning evaluation. Unfortunately, 86% students thought in preparing teaching media needed more time to prepare and a specific knowledge, especially which is interesting and takes less time in making. So, the researchers give an alternatives medium that has a template theme and interesting, slidesgo. It has many advantages, so they can use it in teaching and suit the theme with the material they are going to teach. In the end, most of the students were glad and thought that it made them easy to prepare teaching media and took less time.